Particle size specific distribution of perfluoro alkyl substances in atmospheric particulate matter in Asian cities. Issue 4 (9th March 2017) - Ge, H.; Yamazaki, E.; Yamashita, N.; Taniyasu, S.; Ogata, A.; Furuuchi, M.
Abstract : PM0.1 was found to be a major contributor to the mass fraction of perfluoro alkyl substances, which is more influenced by the type of land use than country differences. Abstract : Seasonal and local characteristics of perfluorinated alkylated substances (PFASs) were examined using size-segregated particles including an ultrafine range. The examination included sampling and analysis of ambient particles collected at four sites located in different environments in three different countries, Japan (Kanazawa and Okinawa), Hong Kong and India. To minimize the evaporation artefacts derived from PFASs during the sampling, an air sampler that permitted particles smaller than 0.1 μm (PM0.1 ) to be separated at a moderate pressure drop (<5–15 kPa), was used for all of the air sampling procedures. In the case of Kanazawa, a local city in Japan, the concentration of PFASs was found to be dominated by carboxylates, especially PFOA, PFNA and PFDA regardless of the particle size and sampling period. Ultrafine particles were found to be the largest contributor to the mass fraction of PFCAs, while the maximum PFOS mass fractions were determined to be in the coarse-sized fractions. The seasonal difference in the total PFAS concentration can be largely attributed to precipitation. The results were basically similar for all sites that were examined. The type of land use may be a more influencing factor on the mass fraction of the PFASs than the country of origin. The dependency of PFAS mass fraction on the specific surface of the particle suggests that ultrafine PFAS particles are segregated, not only by gas deposition but could also be segregated by a mechanism involving compositional dependence or the primary source of the particles. Other possible sources of PFASs, other than from traffic are also possible.